Yield Enhancement and Gap Minimization of Rainfed Pearl Millet by Front Line Demonstration in Churu District of Rajasthan: Yield Enhancement and Gap Minimization by FLD's in Pearl Millet - Ali, Shaukat; Shivran, R. K.; Chandra, Subash; Gupta, Aditi (Annals of Arid Zone, 2023)
KVK, Chandgothi, Churu (Rajasthan) conducted total 175 Front Line Demonstrations on pearlmillet at farmers field in Dingli, Thirpali Chotti, Thirpali Badi, Chandgothi, Sulkhania Chota, Sulkhania Bada, Bas Mamraj, Norangpa villages of Rajgarh Tehshil in Churu District of Rajasthan during five consecutive kharif seasons from 2018 to 2022. The farming situation was rainfed and soil was sandy loam low in nitrogen, medium in phosphorus and medium to high in potash. Assessment of gap was done and on basis of gap assessment, improved recommended technologies of pearlmillet cultivation were demonstrated. On five years average basis, grain yield of pearlmillet was recorded 1349 kg ha-1 under demonstration plot while it was 1081 kg ha-1 in farmer’s practices. On the basis of five year average, 24.75 per cent higher grain yield was recorded under demonstration than the farmer’s practices (Local check). The higher extension gap (267 kg ha-1), technology gap (3351 kg ha-1) and lower technology index (19.77 %) was recorded because of adoption of improved recommended technology in demonstrations. An additional investment of Rs 1240 ha-1 consist with scientific monitoring of demonstration and non–monetary factors resulted in additional return of Rs 6597 ha-1 with an effective gain of Rs 5357 ha-1. On five year average basis, 5.65 incremental benefit : cost ratio (IBCR) was recorded.